Pengaruh Persepsi pada Guru dan Motivasi Berprestasi dalam Pembelajaran Daring terhadap Hasil Belajar Peserta Didik - Haeruddin, Haeruddin; Anwar, Muhammad; Wijaya, mohammad (Program Pasca Sarjana UNM, 2021)
The study aims to discover whether there is an influence of the perceptions on teachers and achievement motivation in online learning on learning outcomes in grade X MIA at SMAN 3 Takalar in academic year 2020/2021 on Chemical Bonding subject. This type of research is correlational by using the design of the influence of independent variable on dependent variable. The study population was students of grade X MIA at SMAN 3 Takalar for academic year 2020/2021 which consisted of 6 classes with 216 students. The research sample was taken by employing random sampling, which obtained one class with 36 students. Hypothesis testing was conducted by employing simple regression analysis and multiple regression analysis. The results of the study indicate that: (1) there is an influence of the perception on teachers in online learning on learning outcomes ingrade X MIA at SMAN 3 Takalar on Chemical Bonding subject with a determination index (R) of 0.269, (2) there is an influence of achievement motivation in online learning on learning outcomes ingrade X MIA at SMAN 3 Takalar on Chemical Bonding subject with a determination index (R) of 0.410, and (3) there is an influence of perception on teachers and achievement motivation collectively in online learning on learning outcomes ingrade X MIA at SMAN 3 Takalar on Chemical Bonding subject with adetermination index (R) of 0.499.